Can Indispensability‐Driven Platonists Be (Serious) Presentists?. (19th July 2013) - Baron, Sam
Abstract In this article I consider what it would take to combine a certain kind of mathematical Platonism with serious presentism. I argue that a Platonist moved to accept the existence of mathematical objects on the basis of an indispensability argument faces a significant challenge if she wishes to accept presentism. This is because, on the one hand, the indispensability argument can be reformulated as a new argument for the existence of past entities and, on the other hand, if one accepts the indispensability argument for mathematical objects then it is hard to resist the analogous argument for the existence of the past.